Richard Filčák and Daniel Škobla, eds. 2022. Odpad ako sociálny problém vo vylúčených rómskych osídleniach [Waste as a social problem in marginalised Romani settlements]. Bratislava: Center for Social and Psychological Sciences at the Slovak Academy of Sciences, Institute of Ethnology and Social Anthropology. - Michal Zálešák (Critical Romani Studies)
In Slovakia, an overwhelming majority of Romani communities live on the periphery of society. Romani settlements lack basic infrastructure such as access to water and sanitation or paved roads. They are most often confined to segregated areas, located on land unsuitable for habitation – on a steep hill, in a flood risk area, next to a waste dump or a big factory and so on. Is this a coincidence? The authors of the publication Odpad ako sociálny problém vo vylúčených rómskych osídleniach (Waste as a social problem in marginalized Romani settlements) published by the Centre for Social and Psychological Sciences at the Slovak Academy of Sciences think otherwise.